2016
DOI: 10.1021/acs.macromol.6b01238
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complex of α-Cyclodextrin with Poly(ethylene glycol) Brush

Abstract: The inclusion complex (IC) of α-cyclodextrin (α-CD) with poly(ethylene glycol) (PEG) brush was investigated by neutron reflectometry and grazing-incidence wide-angle X-ray scattering. When the PEG brush was exposed to 10% aqueous α-CD solution, an IC consisting of randomly oriented α-CD polycrystals appeared. On the other hand, when the PEG brush was exposed to 5% aqueous α-CD solution, a uniform 10-nm-thick IC layer with α-CD stacked perpendicular to the substrate was formed. A 10-nm-thick IC was also found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…It was found that the addition of α-CD affected the structure of the grafted layer, which caused the extension of PEG chains into the bulk, allowing for the formation of a polypseudorotaxane (Figure 7). Recently, Yokoyama et al [150], investigated the formation of inclusion complexes between α-CD and a poly(ethylene glycol) brush and observed a similar phenomenon. It was found that a polypseudorotaxane consisting of randomly oriented α-CD polycrystals appeared when the PEG brush was exposed to a 10% α-CD solution.…”
Section: α-Cyclodextrin/polymer Brush-based Polypseudorotaxane Hydrogelsmentioning
confidence: 81%
“…It was found that the addition of α-CD affected the structure of the grafted layer, which caused the extension of PEG chains into the bulk, allowing for the formation of a polypseudorotaxane (Figure 7). Recently, Yokoyama et al [150], investigated the formation of inclusion complexes between α-CD and a poly(ethylene glycol) brush and observed a similar phenomenon. It was found that a polypseudorotaxane consisting of randomly oriented α-CD polycrystals appeared when the PEG brush was exposed to a 10% α-CD solution.…”
Section: α-Cyclodextrin/polymer Brush-based Polypseudorotaxane Hydrogelsmentioning
confidence: 81%
“…33 PEG chains penetrate into the cavities of α -CD, which are further strengthened via hydrogen bonds between neighboring α -CD on the same PEG chain. 3335 Due to hydrophobic interaction, a crystalline microregion between α -CD can be self-assembled as a physical cross-linking point. Acrylamide (AM) is often used to initiate polymerization into polyacrylamide, which can form covalent network hydrogel under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The first reported host-guest complexation utilizing α-CD is an inclusion complex formation between α-CD and polyethylene glycol (PEG) [16]. PEG chains penetrate into the cavities of α-CDs to form pseudopolyrotaxanes, which are further strengthened via hydrogen bonds between neighboring α-CDs on the same PEG chain[1719].…”
Section: Introductionmentioning
confidence: 99%